1990
DOI: 10.1016/0014-5793(90)80505-d
|View full text |Cite
|
Sign up to set email alerts
|

Agonist binding to purified glycine receptor reconstituted into giant liposomes elicits two types of chloride currents

Abstract: Using 'inside-out' membrane patches obtained from reconstituted giant liposomes containing purified glycine receptor from rat spinal cord, we have detected chloride currents elicited in response to the presence of the agonists glycine or B-alanine. Regardless of the agonist employed, two different patterns of single channel currents could be detected, which differ in their main conductance, complexity of substates and opening frequency. In agreement with the expectations of glycine receptor heterogeneity sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Reconstitution of acetylcholine receptors [47], glycine receptors [48], glutamate receptors [49], KcsA [52], [59] and KirBac1.1 [57] indicate that the proteins are oriented “right-side out”, meaning with the intracellular side facing the bath. The direction of the rectification observed for TcCat (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution of acetylcholine receptors [47], glycine receptors [48], glutamate receptors [49], KcsA [52], [59] and KirBac1.1 [57] indicate that the proteins are oriented “right-side out”, meaning with the intracellular side facing the bath. The direction of the rectification observed for TcCat (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution of the Apical Membrane into Giant Liposomes-Giant liposomes were prepared by submitting a mixture of the isolated apical membrane vesicles and asolectin lipid vesicles to a partial dehydration/ rehydration cycle, as reported by Riquelme et al (25). An aliquot containing 100 -150 g of membrane protein was mixed with 2 ml of a 13 mM (in terms of lipid phosphorus) suspension of the asolectin vesicles.…”
Section: Methodsmentioning
confidence: 99%
“…1) (GRAHAM et al 1981(GRAHAM et al , 1983(GRAHAM et al , 1985PFEIFFER et al 1982;BECKER et al 1986). Upon reconstitution in phospholipid vesicles, the isolated receptor mediates glycine-enhanced, strychnine-sensitive anion translocation (GARCIA-CALVO et al 1989;RIQUELME et al 1990). Upon reconstitution in phospholipid vesicles, the isolated receptor mediates glycine-enhanced, strychnine-sensitive anion translocation (GARCIA-CALVO et al 1989;RIQUELME et al 1990).…”
Section: Receptor Structure and Isoformsmentioning
confidence: 99%
“…A sequence comparison shows that this region of the acetylcholine receptor corresponds to the pre-M1 domain of the highly homologous glycine receptor (BETZ 1990). In fact, analysis of proteolytic fragments of the glycine receptor has shown that UV illumination leads to incorporation of [3H]strychnine into peptide fragments of this ai-subunit region (RUIZ-GOMEZ et al 1990). In fact, analysis of proteolytic fragments of the glycine receptor has shown that UV illumination leads to incorporation of [3H]strychnine into peptide fragments of this ai-subunit region (RUIZ-GOMEZ et al 1990).…”
Section: Ligand Binding Domainsmentioning
confidence: 99%